1994
DOI: 10.1007/bf02751978
|View full text |Cite
|
Sign up to set email alerts
|

Kerosene oil poisoning in children: A hospital-based prospective study in Sri Lanka

Abstract: This is a prospective hospital based study of 526 cases of kerosene oil poisoning seen during a 10 year period. There were 5 cases of deliberate self poisoning and 1 case of attempted homicide. 520 cases were accidental. Pneumonitis occurred in 299 children of whom 253 had vomited after kerosene oil ingestion. There were 3 deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…In this study, male children 61% are more affected than female child, which is similar to Wakil Paswan et al, Kumaravel K S, Lucas et al and Emad Siddique et al [3][4][5][6] Most of the children were from rural places similar to Anwar S et al and Sunilkumar et al, but in contrast to Kumaravel et al study where it was urban dominance. 3,7,8 Kerosene in rural population is stored in bottle containers and children can mistake it for soft drinks.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In this study, male children 61% are more affected than female child, which is similar to Wakil Paswan et al, Kumaravel K S, Lucas et al and Emad Siddique et al [3][4][5][6] Most of the children were from rural places similar to Anwar S et al and Sunilkumar et al, but in contrast to Kumaravel et al study where it was urban dominance. 3,7,8 Kerosene in rural population is stored in bottle containers and children can mistake it for soft drinks.…”
Section: Discussionsupporting
confidence: 78%
“…Regarding central nervous system which is rich in a lipid component myelin, kerosene acts on the compound and causes drowsiness, altered mentation and in severe cases respiratory failure. In our study, Cough was the major symptom present in 61% of children whereas it was found in 85% in Kumaravel study, 90% in Nagi NA et al study 80% in Lucas et al and 82% in Wakil Paswan study and Sunilkumar et al [3][4][5]8,9 Fever was present in 41% cases in this study compared to 69% in Wakil Paswan study, 83.5% in Nagi study and 3% of cases in Kumaravel study. 3,4,9 Vomiting following consumption of kerosene was found in 36% whereas it was found in 69% cases in Kumaravel study and Nagi study showed 60.6%.…”
Section: Discussionmentioning
confidence: 42%
“…Of the hydrocarbon poisonings, majority (60.87%) were from kerosene ingestion, similar to study done by [24].The reason could be attributed to kerosene being mistaken for water [16,23,40,31].…”
Section: Discussion:-supporting
confidence: 76%
“…It is a serious cause of poisoning in the lower socio-economic group 2,5 . In our study 72% of the families were in the lower socio-economic group.…”
Section: Discussionmentioning
confidence: 99%